2014
DOI: 10.1002/bab.1162
|View full text |Cite
|
Sign up to set email alerts
|

Ormosil gels doped with engineered catechol 1,2 dioxygenases for chlorocatechol bioremediation

Abstract: Enzymes entrapped in wet, nanoporous silica gel have great potential as bioreactors for bioremediation because of their improved thermal, chemical, and mechanical stability with respect to enzymes in solution. The B isozyme of catechol 1,2 dioxygenase from Acinetobacter radioresistens and its mutants of Leu69 and Ala72, designed for an increased reactivity toward the environmental pollutant chlorocatechols, were encapsulated using alkoxysilanes and alkyl alkoxysilanes as precursors in varying proportions. Enca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…As in solution, the unproductive binding of catechol was observed under anaerobic conditions. Spectra were also correlated with the three dimensional structures of the wild type and two mutants exhibiting higher specificity for chloro cathecols and designed as the basis for bioreactors to be used in bioremediation (Micalella et al, 2014 ). Overall, the consistency of the spectroscopic properties of Ar-1,2-CTD in solution and in the crystalline state indicated that Fe(III) coordination and ligand binding observed through X-ray crystallography reflected those of the enzyme in solution.…”
Section: Examples Of Protein Structure-function Correlation In the Crmentioning
confidence: 99%
“…As in solution, the unproductive binding of catechol was observed under anaerobic conditions. Spectra were also correlated with the three dimensional structures of the wild type and two mutants exhibiting higher specificity for chloro cathecols and designed as the basis for bioreactors to be used in bioremediation (Micalella et al, 2014 ). Overall, the consistency of the spectroscopic properties of Ar-1,2-CTD in solution and in the crystalline state indicated that Fe(III) coordination and ligand binding observed through X-ray crystallography reflected those of the enzyme in solution.…”
Section: Examples Of Protein Structure-function Correlation In the Crmentioning
confidence: 99%